ANALISIS DAMPAK PAKAN FERMENTATIF TERHADAP PENGGEMUKAN SAPI POTONG : Indonesia - MILANA, LIA; Imanudin, Oki Imanudin; Juliar, Eka; Saparinda, Wulan (Universitas Majalengka, 2023)
In the cattle fattening business, feed is the main factor determining cattle growth. Providing quality feed is a challenge for ruminant breeders, both large ruminants and small ruminants, especially during the dry season where availability is very limited. Therefore, breeders are required to create other alternatives for providing quality feed, with good shelf life, at lower costs. One application of simple technology that could be a solution is through feed fermentation. This research aims to analyze: the effect of fermented feed on cattle fattening performance. The material used was 15 cows, consisting of 8 imported/foreign crossbreed cattle and 7 local cattle. The location of this fattening process is carried out at the Ibnu Hikam Tani Farmer's Cage, Kulur Sindangkasih Village, Majalengka. The method used is Operational Research (RO). The results of the research showed that by using fermented feed, the increase in body weight (ADG) of foreign breed cattle was 0.5-0.7 kg per day, while the growth of local cattle was 0.5 kg per day. Meanwhile, the average daily feed cost is IDR 20,000-25,000 per day per head. Farmers' perceptions vary regarding the price of feed and feed ingredients. Even though this self-mixed fermented feed is still below SNI standards, it does not reduce the nutritional quality for the nutritional intake needed by ruminants. This research concluded that by using fermented feed, foreign-breed cattle absorb more nutrients than local cattle. So it is recommended to improve feed quality by adding or changing the feed formula currently used.